Pengaruh Model Problem Based Learning Terhadap Motivasi dan Hasil Belajar IPS Kelas V Sekolah Dasar - Samiati Samiati; Anwar Senen (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The Teacher's ability to create a good learning environment greatly affects how well students learn and the kind of people they become. How much students learn depends a lot on their desire to learn. This desire has a big impact on how effective their learning is. This study looked at how using the PBL learning model affects the motivation to learn social studies among fifth-grade students in Gugus II Panjatan. It also checked how the PBL model affects their social studies learning results and how it influences both their motivation and learning outcomes. The study used a quasi-experimental design with a pretest and posttest, and included two groups that weren't exactly the same. The experiment took place in two fifth-grade classes at SDN Depok. One class used the PBL model, and the other used the Direct Instruction model. Information was collected through observations, questionnaires about learning motivation, and tests on learning outcomes. The data was analyzed using t-tests and ANOVA. The results showed that students in the PBL class had an average motivation score of 61.69, while those in the DI class had 57.95. The PBL class also had an average learning score of 76.25 compared to 65.50 for the DI class. These results show that using the PBL model has a very strong effect on both the motivation and learning results of fifth-grade students in Gugus II Panjatan.